QUALIDADE DAS RESPOSTAS DAS TELECONSULTORIAS DO NÚCLEO DE TELESSAUDE ESTADUAL DO MARANHÃO - LIMA, Cirlandio Coutinho de (2019)
Brazilian Telehealth is a program from the Brazilian Ministry of Health that seeks to integrate teaching and service through the use of Information and Communication Technologies, with the intention of qualifying Primary Health Care services in the Unified Health System. The Telehealth Center of the University Hospital of the Federal University of Maranhão is responsible for the promotion of Telehealth activities in the state of Maranhão where it conducts teleconsulting activities that are registered consultations among health workers, professionals and managers through bidirectional telecommunication instruments, in order to answer questions about clinical procedures, health activities and issues related to the work process. Objective: To evaluate the quality of the teleconsulting response provided by Maranhão Telehealth State Center. Methods: Descriptive and analytical study with quantitative approach. The quality of response was measured by audit that verified the adequacy of the response according to the guidelines of Brazil Telehealth Networks Program. The resolvability of the response and the applicant's satisfaction were verified by means of a form integrated with teleconsulting. The association between response quality and the applicant's degree of satisfaction was tested by Fisher's Exact, considering the significance level of 5% (p <0.05). Results: 88% of applicants have had their doubts cleared up completely; 98.2% reported being satisfied or very satisfied. As for the quality of the answer, 85% were classified as good, very good and excellent. It is noteworthy that 44% obtained excellent evaluation. There was a statistically significant association between the quality of the teleconsulting response and the applicant's degree of satisfaction (p = 0.001). Conclusion: The quality of the teleconsulting responses were considered great. The applicants' questions were solved and they were way satisfied with the results.